THE EFFECT OF GOAT MANURE ENRICHED WITH BIOACTIVATORS AND TRICHODERMA DOSE ON THE GROWTH AND YIELD OF PURPLE CORN (Zea mays var. ceratine Kulesh): PENGARUH PUPUK KANDANG KAMBING YANG DIPERKAYA DENGAN BIOAKTIVATOR DAN DOSIS TRICHODERMA TERHADAP PERTUMBUHAN DAN HASIL JAGUNG UNGU (Zea mays var ceratine Kulesh) - KURNIA SAFITRI, ISNIN; AJAT, UJANG; PODESTA, FIANA; HARINI, RIRIN; SURYADI; FITRIANI, DWI (Agriculture, 2025)
The purpose of this study was to determine the effect of goat manure enriched with bioactivator and trichoderma dosage on the growth and yield of purple corn (Zea mays var ceratine Kulesh). The design used was a Completely Randomized Design (CRD) consisting of 2 factors, namely the first factor of goat manure enriched with bioactivator (A) A0 (standard NPK), A1 (goat manure with stale rice bioactivator), A2 (goat manure with cow rumen bioactivator), A3 (goat manure with yeast bioactivator), and the second factor was the dose of Trichoderma T0 (without Trichoderma dosage), T1 (15 grams of Trichoderma), T2 (30 grams of Trichoderma), T3 (45 grams of Trichoderma). Each treatment was repeated 3 times. The results of the data were analyzed using Analysis of Variance (ANOVA) if there was no significant difference, a further Duncan's Multiple Range Taste (DMRT) test was carried out at a level of 5%. Based on the research results, the treatment of goat manure enriched with bioactivator of stale rice, rumen, and yeast significantly affected plant height at 14 hst, 28 hst and 42 hst, number of leaves at 14 hst, 42 hst, stem diameter at 28 hst, 42 hst and 56 hst, plant dry weight, root wet weight, and root dry weight. While the dose of Trichoderma had no significant effect on all parameters. and there was no interaction between goat manure and the dose of Trichoderma.